Comparative Transcriptome Analysis of Shewanella putrefaciens WS13 Biofilms Under Cold Stress - Yan, Jun; Yang, Zhijun; Xie, Jing (Frontiers in Cellular and Infection Microbiology, 2022)
S. putrefaciens is easy to form a biofilm. The biofilm enhances the environmental tolerance of the microbial cells in the biofilm. According to previous study, the biofilm formed by S. putrefaciens WS13 under low temperature (4 oC) has larger biomass and tighter structure than the biofilm formed at the optimum growth temperature (30 oC). Therefore, we speculated that the biofilm is beneficial to the survival of S. putrefaciens WS13 under cold stress. In this study, transcriptomics technology was used to analyze the gene expression of the cells in the biofilm formed by S. putrefaciens WS13 under refrigerating temperature and optimal temperature. The results indicated that a total of 761 genes were differentially expressed, of which 497 were significantly up-regulated and 264 were significantly down-regulated, which were enriched in 28 pathways. The qRT-PCR results were in accordance with RNA sequencing results which validated the conclusions. The DEGs that relate to biofilm formation, amino acid metabolism, two-component system, and quorum sensing were essential for the biofilm formation of S. putrefaciens WS13 under cold stress. This work provides valuable insights into the transcriptional regulation in biofilm cells under cold stress and laid a theoretical foundation for the targeted inhibition of S. putrefaciens biofilm.